1991
DOI: 10.1152/jappl.1991.70.5.2080
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway cooling and l-menthol reduce ventilation in the guinea pig

Abstract: Cooling of the upper airway, which stimulates specific cold receptors and inhibits laryngeal mechanoreceptors, reduces respiratory activity in unanesthetized humans and anesthetized animals. This study shows that laryngeal cooling affects the pattern of breathing in the guinea pig and assesses the potential role of cold receptors in this response by using a specific stimulant of cold receptors (l-menthol). The response to airflows (30 ml/s, 10-s duration) through the isolated upper airway was studied in 23 ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…Menthol is known to stimulate cold receptors and to produce a cooling sensation as well as local anesthesia. In animals, menthol inhalation results in longer air retention time in the lungs (Orani et al, 1991;Sant'Ambrogio et al, 1991). Furthermore, many African-Americans report the ease of inhalation and ability to inhale more deeply as reasons for smoking mentholated cigarettes (Hymowitz et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Menthol is known to stimulate cold receptors and to produce a cooling sensation as well as local anesthesia. In animals, menthol inhalation results in longer air retention time in the lungs (Orani et al, 1991;Sant'Ambrogio et al, 1991). Furthermore, many African-Americans report the ease of inhalation and ability to inhale more deeply as reasons for smoking mentholated cigarettes (Hymowitz et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…UA cooling inhibits breathing in adult cats [5], guineapigs [25] and rats [7], and also in neonatal dogs [26] and guinea-pigs [12]. On the other hand, laryngeal cooling has no effect on breathing in adult dogs [3]; and JAMMES et al [4] observed no significant changes in ventilation with laryngeal cooling in adult cats.…”
Section: Discussionmentioning
confidence: 99%
“…Menthol stimulates cold receptors, with the resulting sensation of coolness perceived not only in the mouth and pharynx but also in the lungs (Eccles, 1994(Eccles, , 2000. Stimulation of laryngeal cold receptors may reduce airway irritation (Orani, Anderson, Sant'Ambrogio, & Sant'Ambrogio, 1991). This sensation of coolness might result in deeper inhalation, but because of the difficulty in precisely measuring the inhalation phase of smoking, this issue has not been studied adequately.…”
Section: Why It Is Important To Study Menthol Cigarettesmentioning
confidence: 99%